Land subsidence susceptibility mapping using PWRSTFAL framework and analytic hierarchy process: fuzzy method (case study: Damaneh-Daran Plain in the west of Isfahan Province, Iran) - Chitsazan, Manouchehr; Rahmani, Gholamreza; Ghafoury, Hamidreza (Environmental monitoring and assessment, 2022)
Land subsidence susceptibility mapping is a necessary prerequisite for land subsidence management. Proper assessment of land subsidence requires determining parameters affecting subsidence to discover the spatial relationships with subsidence. For this purpose, two frameworks were prepared, according to the land site subsidence, eight parameters affecting the subsidence in the Damaneh-Daran plain. In the first framework, eight parameters including annual groundwater level drawdown, aquifer medium, land use, discharge, aquifer saturation thickness, net recharge, fault proximity and topography called PWRSTFAL based on weighting parameters and the second model based on optimization and compatibility of eight active layers on subsidence, were prepared by AHP-fuzzy method and the final map of subsidence vulnerability obtained. Radar images and the InSAR method validated the methods. The results show that both maps show a good correlation with radar data. Still, the map prepared by the AHP-fuzzy method offers the highest correlation with radar data and subsidence in the plain. It separates subsidence vulnerability in more detail on the whole surface of the plain. According to this model, most plain areas, especially the eastern part, are subject to subsidence, and management programs should control subsidence. The results ROC diagram obtained from the performance of the PWRSTFAL framework based on the AHP-fuzzy method was more promising than the ordinary PWRSTFAL framework.